Biochar gasification performance in fluidized bed reactor - Wan Ab. Karim Ghani, Wan Azlina; Mohd Salleh, Mohamad Amran; Alias, Azil Bahari (2015)
An experimental study of air gasification of palm kernel shell-derived biochar (PKB) was conducted in a bench-scale fluidized bed gasifier (FBG) with 50 mm diameter and 850 mm height. The operating conditions studied varied in the following range; reaction temperature in gasification zone (600˚C-1000˚C), feeding rate (0.002-0.017 kg/h) and particle size (0.2-3 mm). The carbon conversion efficiencies were also calculated to evaluate the gasification performance. The results obtained have revealed that the temperature and equivalence ratio are the most important parameters in the gasification process. Increasing temperature favored the hydrogen production and gas yield. Over the range of operating condition examined maximum hydrogen (H2), carbon monoxide (CO), methane (CH4) content reaches to 27 vol%, 7.4 vol% and 10.80 vol%, respectively. In conclusion, palm kernel shell biochar is a potential candidate as an alternative renewable energy source for power generation.